The Gravity of Cross-border R&D Expenditure - Bernhard Dachs; Sandra M. Leitner; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2012)
While up to the 1990s, R&D was still 'an important case of non-globalization' (Patel and Pavitt 1991), the internationalization of business R&D activities has accelerated significantly during the past two decades. R&D activities of foreign affiliates have become one of the most dynamic elements of the process of globalization. Until recently, the main recipients of cross-border R&D expenditure were developed countries, though new players have emerged lately, particularly in Asia. Against that backdrop, the paper applies a recently compiled novel data set on R&D expenditure of foreign-owned firms in the manufacturing sectors of a set of OECD countries and identifies specific home- and host-country characteristics that are conducive or obstructive to cross-border R&D expenditure of foreign affiliates. The results point to the pivotal role of market size and of cultural, physical and technological proximity for R&D efforts of foreign-owned firms. Moreover, the analysis demonstrates that sufficient human capital and strong indigenous technological capabilities in the host country tend to be conducive to R&D activities of foreign affiliates. In contrast, a rich human capital base in the home country is obstructive to the process of R&D internationalization. Geographic distance turns out to be a strong deterrent.
Keywords: F23; O32; L6; 330; internationalization of R&D; multinational firms; gravity model